Channel selection and retailer dual-channel coordination in the e-commerce context. (2nd July 2016) - Liu, Tingting; Xu, Qing; Ma, Cheng
Abstract: This paper discusses the issues about the channel selection in the e-commerce context. In order to identify whether the manufacturer or the retailer is more suitable to open the direct channel, we establish a game model and compare the whole channel members' profits and the total supply chain's profit in four different channel structures. In addition, we study optimal market strategies of the manufacturer and the retailer in the dual-channel model of retailer, and design a revenue sharing contract – the manufacturer provides products to retailer with a low price, in return, the retailer shares part of profit to the manufacturer – as an additional strategic tool for full channel coordination. Our findings indicate that this revenue sharing contract can fully coordinate all the distribution channels so that the profit of each member in supply chain increases. In some sense, results of our research are of some importance for the channel members to choose distribution channels and dual-channel coordination.